Assessing and explaining the relative efficiency of local government - Afonso, António (2022)
We assess the relative efficiency of local municipalities using Data Envelopment Analysis and parametric analysis. As an output measure we compute a composite local government indicator of municipal performance, using data for Portuguese municipalities. This allows assessing the extent of possible municipal improvement relative to the “best-practice” frontier. Our results suggest that most municipalities could improve performance without necessarily increasing municipal spending. In a second stage efficiency scores are explained by means of a Tobit analysis with a set of relevant explanatory socio-economic factors playing the role of non-discretionary inputs, such as education and per capita purchasing power.